Intracerebral Hemorrhage: The Effects of Aging on Brain Injury - Watson, Noah; Bonsack, Frederick; Sukumari-Ramesh, Sangeetha (Frontiers in Aging Neuroscience, 2022)
Intracerebral hemorrhage (ICH) is a devastating subtype of stroke with high rates of mortality and morbidity. ICH patients often suffer devastating and debilitating neurological impairments, from which the majority of victims are unable to fully recover to functional independence. Unfortunately, there is no established medical therapy for ICH, which is partly attributed to the lack of understanding of the complex pathology of the disorder. Despite advanced age being a major risk factor of ICH, most preclinical studies on ICH employed young animal subjects. Due to this discrepancy, the molecular level changes in the aging brain after ICH are largely unknown, limiting the translation of preclinical studies into potential human treatments. The purpose of this review is to highlight the effects of advanced age on ICH- induced brain injury and recovery and to draw attention to current knowledge gaps, which warrant further investigation.